Strangulation of a Meckel’s diverticulum in a femoral hernia (Littre’s hernia) - Misiak, Piotr; Piskorz, Łukasz; Kutwin, Leszek; Jabłoński, Sławomir; Kordiak, Jacek; Brocki, Marian (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Femoral hernia is usually presented as a flexible, round, domed shape lying on the medial side of the thigh about 2–3 cm below the inguinal ligament. Among the external hernias, femoral hernia is the second most common inguinal hernia. Its prevalence reaches 20%. Among all inguinal hernias, femoral hernias are characterised by a high level of incarceration and strangulation. This can be as high as 60%. We would like to present a case of 71-year-old patient who was admitted to the Clinic urgently due to strangulation of Meckel’s diverticulum in a right-sided femoral hernia. Strangulation of Meckel’s diverticulum in femoral hernia is an extremely rare entity. It was described for the very first time in 1700 by Littre.